1978
DOI: 10.1111/j.1600-0447.1978.tb00239.x
|View full text |Cite
|
Sign up to set email alerts
|

14‐year outcome in early schizophrenia

Abstract: Of 45 first admission schizophrenics from 1963, an incidence by first admission group for northern Alberta, 43 were followed-up 14 years later. Based on these figures the expectancy was found to be 0.49%. The proportion of patients who were married was less than expected in comparison with the general population, but amongst the married, fertility was probably comparable to the population's. At follow-up about half the patients were managing well with little or no disability, one quarter had moderate to marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
2

Year Published

1984
1984
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 29 publications
4
26
0
2
Order By: Relevance
“…Thirty seven discrete-core studies report rates only for persons [31,33,45-49,55-57,59,61,65,71,73,75,76,78,79,85,86,88,91,93-96,99,103,104,107,112,114,121,124-126,180,190], 13 report rates only for males and females [41,50,52,53,67,74,82,102,111,116,123,188,189], and 18 studies report rates for persons, males, and females [13,51,54,58,60,69,70,72,77,80,83,84,92,97,98,100,101,106]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty seven discrete-core studies report rates only for persons [31,33,45-49,55-57,59,61,65,71,73,75,76,78,79,85,86,88,91,93-96,99,103,104,107,112,114,121,124-126,180,190], 13 report rates only for males and females [41,50,52,53,67,74,82,102,111,116,123,188,189], and 18 studies report rates for persons, males, and females [13,51,54,58,60,69,70,72,77,80,83,84,92,97,98,100,101,106]. …”
Section: Resultsmentioning
confidence: 99%
“…The rate ratio curve is normally distributed. While there were nine studies with rate ratios less than one [13,41,51,60,69,70,72,83,106,111], over 84% of rates lie above one, with a median value (10% to 90% quantiles) of 1.40 (0.9, 2.4). In a random-effects model for the logarithm of the rates, the sex-difference is significant ( F 1,30 = 76.8, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the methodology used at the inception of the study as well as the findings at 10-and 14-year follow-ups have been reported by Bland et al 8,9,15,16 Ethics approval was received from Alberta Hospital Edmonton and Alberta Hospital Ponoka (the 2 institutions initially involved in treating the patients) and from the University of Alberta.…”
Section: Methodsmentioning
confidence: 99%
“…Indicators were scored below 1 if they fell within the definition of prodromal symptoms and behaviours, such as hints of positive signs (illusions, magical thinking, ideas of reference), moodiness, cognitive problems, and social withdrawal. The ratings were made by one author who had interviewed each patient for the 10-and 14-year follow-up studies 8,15 and, for our study, had interviewed each patient who was alive at the close of the 34-year follow-up. Additional information was systematically collected from hospital files, treatment records, and interviews with family members.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation